Batu Nabau: a rock formation phenomenon in the context of legends and intangible heritage of the Iban people in Sarawak - Gregory Kiyai @ Keai (Penerbit Universiti Kebangsaan Malaysia, 2025)
Batu Nabau, a prominent rock formation in Engkelili, Sri Aman Sarawak, holds significant cultural and mythological importance for the Iban people, believed to be the petrified remains of a giant serpent. Despite its sacred status and symbolic value, detailed documentation and research on Batu Nabau are limited. This study investigates Batu Nabau's role in Iban folklore and its contribution to preserving intangible cultural heritage in Iban identity. Employing qualitative methods, the research utilizes an explanatory approach with data collected from primary and secondary sources, including observations and existing literature. Visual analysis of cultural artifacts and oral traditions reveals Batu Nabau's integral role in the Iban community, reflecting their mythology and identity. The findings highlight Batu Nabau’s function as a cultural memory hub and its influence on Iban rituals and community cohesion. Future studies should aim to thoroughly document and analyze the influence of Batu Nabau on Iban cultural practices, exploring its potential as a key element in heritage conservation and culture preservation. The Batu Nabau research is essential in understanding the Iban identity, especially in how traditional stories, myths, and historical events interact with contemporary views on self and community.